2017
DOI: 10.1136/bmjquality.u220636.w7996
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the quality improvement impact of the Global Tracheostomy Collaborative in four diverse NHS hospitals

Abstract: Tracheostomies are predominantly used in Head & Neck Surgery and the critically ill. The needs of these complex patients frequently cross traditional speciality working boundaries and locations and any resulting airway problems can rapidly lead to significant harm. The Global Tracheostomy Collaborative (GTC) was formed in 2012 with the aim of bringing together international expertise in tracheostomy care in order to bring about rapid adoption of best practices and to improve the quality and safety of care to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 16 publications
1
44
0
Order By: Relevance
“…While the primary aim of these guidelines is to improve the emergency management of paediatric tracheostomy emergencies, wider developments include addressing the safety and quality of care, with the aim of reducing the incidence of airway emergencies. Initiatives such as the Global Tracheostomy (Quality Improvement) Collaborative (http://www.globaltrach.org) can support organisational improvements and by collecting patient‐level metrics, quantify the effectiveness of care bundles, protocols, and of training, equipping and supporting staff in delivering high‐quality care . Improving transitional and community paediatric tracheostomy care may also improve the safety and quality of care and reduce emergency department visits .…”
Section: Discussionmentioning
confidence: 99%
“…While the primary aim of these guidelines is to improve the emergency management of paediatric tracheostomy emergencies, wider developments include addressing the safety and quality of care, with the aim of reducing the incidence of airway emergencies. Initiatives such as the Global Tracheostomy (Quality Improvement) Collaborative (http://www.globaltrach.org) can support organisational improvements and by collecting patient‐level metrics, quantify the effectiveness of care bundles, protocols, and of training, equipping and supporting staff in delivering high‐quality care . Improving transitional and community paediatric tracheostomy care may also improve the safety and quality of care and reduce emergency department visits .…”
Section: Discussionmentioning
confidence: 99%
“…The Global Tracheostomy Collaborative (GTC) includes 45 member hospitals around the world working to eliminate catastrophic tracheostomy‐related events and improving the lives of patients with a tracheostomy. Implementation of GTC drivers decreased length of stay across four National Health Service hospitals . Some authors have suggested that tracheostomy‐related catastrophic events might be considered never events, as most events involve absence of preventive/rescue measures or shortfalls in training and staffing .…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of GTC drivers decreased length of stay across four National Health Service hospitals. 25 Some authors have suggested that tracheostomy-related catastrophic events might be considered never events, as most events involve absence of preventive/rescue measures or shortfalls in training and staffing. 26 Although some causes of tracheostomy-related mortality, such as tracheoinnominate fistula, are very difficult to prevent, others, such as tracheotomy wounds, have been characterized as never events based on analogy to decubital ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…The National Tracheostomy Safety Project (NTSP) has published strategies to manage and prevent airway emergencies in patients with tracheostomies and laryngectomies. 1,2 However, front-line healthcare professionals most likely to benefit from guidance may not have access to or are unlikely to read publications in traditional medical literature. To improve dissemination of such guidelines, The Health Foundation launched Evidence into Practice in 2017.…”
mentioning
confidence: 99%
“…The Portsmouth physiological and operative severity score for the enumeration of mortality (P-POSSUM), surgical risk scale (SRS), and surgical outcome risk tool (SORT) have previously been used to predict 30-day perioperative mortality. 1,2 However, their accuracy compared with clinical judgement alone remains unknown.…”
mentioning
confidence: 99%